Implikasi Perubahan Data Pribadi oleh Subjek Data Terhadap Keabsahan Perjanjian Kredit dan Jaminan Hak Tanggungan Perspektif UU Nomor 27 Tahun 2022 - Dewi, Anggraeni Puspa; Suhariyanto, Didik; Hartana Hartana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the legal consequences arising from changes to personal data made by data subjects on the validity of collateral that has been used as security for credit, as well as to examine the forms of legal protection that may be granted to creditors. Changes to personal data such as identity, address, and the debtor’s legal status may lead to legal uncertainty regarding the validity of credit security agreements, particularly those involving Hak Tanggungan (mortgage rights). In this research, the author employs a normative juridical method using statutory and conceptual approaches. The findings of this study show that changes to personal data without notification or updates to the security documents have the potential to create administrative discrepancies and legal risks for creditors during the execution of the collateral. Legal protection for creditors needs to be strengthened through the regulation of the debtor’s obligation to report any changes in personal data, updates to the security certificates, and clear provisions outlined in the credit agreement. Accordingly, legal certainty between the creditor and the debtor can be maintained in line with the implementation of Law Number 27 of 2022 on Personal Data Protection.